Local community attitudes toward forests outside protected areas in India: impact of legal awareness, trust, and participation - Macura, B.; Zorondo-Rodríguez, F.; Grau-Satorras, M.; Demps, K.; Laval, M.; García, C.A.; Reyes García, Victoria (2011)
The success of long-term sustainable management of natural resources depends on local people’s support. Assessing local people’s attitudes, taking into account their needs, and respecting their opinions should become a management priority. In India, in the last 20 years, community needs and aspirations in forest management were handled through Joint Forest Management with varying degrees of success. Recently, the Forest Rights Act (2006) was passed to recognize and vest forest rights in forest dwelling communities. This major policy development is still in implementation, but little is known about how this devolution process will affect people’s attitudes toward forests. In this paper, we analyze associations between attitudes toward state controlled forests (Reserved Forests) and (i) awareness about the Forest Right Act, (ii) attitudes toward the State Forest Department, and (iii) participation in forest management groups of mostly tribal forest dwellers in the district of Kodagu (Karnataka). We collected information with a structured questionnaire among 247 villagers living under three different land tenure and management regimes: (1) private coffee plantations, (2) Reserved Forest, and (3) National Park. The results of the multivariate analyses show that people are more likely to appreciate Reserved Forests if they have more knowledge about the Forest Rights Act and if they have positive attitudes toward the State Forest Department. A sobering result in our sample is that participation in formal forest management groups is negatively associated to attitudes toward Reserved Forests, suggesting the Joint Forest Management model doesn’t necessarily help the transition from coercion to consent. Increasing local people awareness about their rights and improving their relations with the formal forest stewards remain priorities for sustainable forest management to emerge in India.